Computer science and engineering department, Faculty of Engineering, University of Chittagong, Bangladesh - Rahman, Atiqur; Ufiteyezub, Emmanuel (Penerbit Universiti Kebangsaan Malaysia, 2023)
Due to the growing of the city population, progressively more vehicles are moving through the urban area in demand for parking lots, often causal to the worldwide difficulty of traffic jams. The existing parking system does not have a decent method to know whether the slots are empty or not. So, the user/driver has to rummage around to find an empty slot. As a result, there is a lot of traffic jam on the road, which destroys the normal life of the people. This paper focuses on how to improve the existing parking lot’s occupancy detection system in a scientific way and proposed the smart parking occupancy detection system named rPark. rPark is offered as an innovative technique for detecting parking occupancy. For the initial stage, Ultra High Frequency static RFID chips are installed on the asphalt and cross-examined by RFID interrogator antennas over the parking spots to notice the usage status. A maximum of the difficulties of the existing state-of-the-art parking usage recognition methods are not existing in this scheme. rPark was examined and employed to illustrate an experimental analysis in a physical domain out-of-doors parking spot and has been verified to have a system’s parking detection accuracy is about 100%.